FACTORS OF TOURISM DEVELOPMENT IN LESS-FAVOURED AREAS OF THE PODKARPACKIE VOIVODSHIP - Baran, Ewa; Grzebyk, Bogumiła (Acta Scientiarum Polonorum. Oeconomia, 2010)
With regard to Podkarpacie, less-favoured areas (LFA) denote the areas threatened with socio-economic marginalization yet possessing unique and invaluable resources of the natural environment. Polish membership in the European Union and adoption of the rural development policy creates favourable conditions for tourism growth as a form of unlocking its LFA endogenic potential. The paper attempts to evaluate the level and determinants of the LFA tourism development at the district level. For this purpose an analysis of the environmental and tourist values has been carried out with special emphasis on the quality of the relevant infrastructure. The level of tourism development is evaluated on the basis of the synthetic index.